Discovery of Point Mutations in the Voltage-Gated Sodium Channel from African Aedes aegypti Populations: Potential Phylogenetic Reasons for Gene Introgression. - Hitoshi Kawada; Yukiko Higa; Kyoko Futami; Yuto Muranami; Emiko Kawashima; Joseph H N Osei; Kojo Yirenkyi Sakyi; Samuel Dadzie; Dziedzom K de Souza; Maxwell Appawu; Nobuo Ohta; Takashi Suzuki; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Yellow fever is endemic in some countries in Africa, and Aedes aegpyti is one of the most important vectors implicated in the outbreak. The mapping of the nation-wide distribution and the detection of insecticide resistance of vector mosquitoes will provide the beneficial information for forecasting of dengue and yellow fever outbreaks and effective control measures. METHODOLOGY/PRINCIPAL FINDINGS:High resistance to DDT was observed in all mosquito colonies collected in Ghana. The resistance and the possible existence of resistance or tolerance to permethrin were suspected in some colonies. High frequencies of point mutations at the voltage-gated sodium channel (F1534C) and one heterozygote of the other mutation (V1016I) were detected, and this is the first detection on the African continent. The frequency of F1534C allele and the ratio of F1534C homozygotes in Ae. aegypti aegypti (Aaa) were significantly higher than those in Ae. aegypti formosus (Aaf). We could detect the two types of introns between exon 20 and 21, and the F1534C mutations were strongly linked with one type of intron, which was commonly found in South East Asian and South and Central American countries, suggesting the possibility that this mutation was introduced from other continents or convergently selected after the introgression of Aaa genes from the above area. CONCLUSIONS/SIGNIFICANCE:The worldwide eradication programs in 1940s and 1950s might have caused high selection pressure on the mosquito populations and expanded the distribution of insecticide-resistant Ae. aegypti populations. Selection of the F1534C point mutation could be hypothesized to have taken place during this period. The selection of the resistant population of Ae. aegypti with the point mutation of F1534C, and the worldwide transportation of vector mosquitoes in accordance with human activity such as trading of used tires, might result in the widespread distribution of F1534C point mutation in tropical countries.